ECE and DISP processes at channel electrodes: Analytical theory - Leslie, WM; Alden, J; Compton, R; Silk, T (1996)
Analytical theory is developed for ECE and DISP1 reactions occurring at channel electrodes. Simple expressions are presented which allow the ready mechanistic interpretation of experimental data and the deduction of corresponding rate constants. These are shown to be in excellent agreement with numerical simulations and with experiments conducted on the reductions of o-bromonitrobenzene in dimethylformamide solution and of p-bromonitrobenzene in acetonitrile in the presence of light of wavelength 325 nm. © 1996 American Chemical Society.